Human relation skills of school administrators in area IV, Division of Batangas : an assessment - Falqueza, Joepi F. (Manila : National University, 2005)
This study was conducted to determine the level of the school administrator's human relation skills as assessed by themselves and by the teachers in Area IV, Division of Batangas during the school year 2004-2005.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Letter of Request -- Questionnaire -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.